2018
DOI: 10.3390/antiox7010017
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Response to Exercise and Its Modulation

Abstract: Strenuous exercise induces such inflammatory responses as leukocytosis (neutrophilia) and symptoms as delayed-onset muscle soreness and swelling. However, the association between inflammatory mediator cytokines and oxidative stress is not fully delineated. Herein, in addition to basic background information on cytokines, research findings on exertional effects on cytokine release and the underlying mechanisms and triggers are introduced. Then, the associations among cytokine responses, oxidative stress, and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 39 publications
(75 reference statements)
1
106
0
1
Order By: Relevance
“…In young non-pregnant women (age 22 years, BMI 23.5 kg/m 2 ; unpublished data from the ACTIBATE project), 45 these associations were also found to be non-significant. These results might be plausible since muscle-derived IL-8 (at mRNA and protein levels), during and after strenuous exercise, 37,38,46 exerts its effects locally in the myocytes and endothelium vascular cells (in the contracting muscle) rather than in systemic circulation. 39,46 Paradoxically, our results showed that meeting the PA recommendations was positively associated with circulating IL-8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In young non-pregnant women (age 22 years, BMI 23.5 kg/m 2 ; unpublished data from the ACTIBATE project), 45 these associations were also found to be non-significant. These results might be plausible since muscle-derived IL-8 (at mRNA and protein levels), during and after strenuous exercise, 37,38,46 exerts its effects locally in the myocytes and endothelium vascular cells (in the contracting muscle) rather than in systemic circulation. 39,46 Paradoxically, our results showed that meeting the PA recommendations was positively associated with circulating IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results are supported by previous studies in non-pregnant women, 33,35,36 except for MVPA, which was inversely associated with TNF-α. 33 Regarding exercise in the general population, most studies have shown that acute strenuous exercise normally has either no effect or a slight effect on circulating TNF-α, 37,38 and increases IL-10 concentrations (partly mediated by IL-6). [37][38][39] However, in pregnancy, regular exercise might suppress the alterations observed in TNF-α along each trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the infiltration of neutrophils into tissues causes subsequent inflammation and oxidative stress and is also partially involved in muscle damage and DOMS [6,7,13,18,27]. Therefore, measuring the dynamics and function of neutrophils are crucial in elucidating the mechanism of the subsequent chain reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced muscle damage (EIMD), which is one of the reasons for DOMS, is caused by not only mechanical factors, but also non-mechanical factors [3]. One possible mechanism causing muscle damage is the invasion of leukocytes, especially phagocytes, including neutrophils and macrophages, into skeletal muscle [4,5,6]. Phagocytes infiltrating muscle tissue play essential roles in tissue repair, such as protein degradation and removal of cellular debris, whereas activated phagocytes release pro-inflammatory cytokines and reactive oxygen species (ROS), and induce inflammation as well as myofiber membrane lysis [4,7].…”
Section: Introductionmentioning
confidence: 99%